Peranan Sektor Pertanian Dan Industri Pengolahan Dalam Perekonomian Provinsi Sumatera Barat Dengan Pendekatan Analisis Input-Output - Annisa Meirani; Doni Satria (Media Riset Ekonomi Pembangunan (MedREP), 2024)
The purpose of this study is to examine how the agricultural and manufacturing sectors contribute to the West Sumatra Province's economy. In addition to analyzing the multiplier effects on output and income in West Sumatra Province, the research will also look at the connections between the manufacturing and agricultural sectors and other economic sectors. It will also analyze the manufacturing and agricultural sectors' degree of sensitivity and dissemination power. The 2016 West Sumatra Input-Output table, which is classified into 17 and 52 business sectors, was analyzed as the study technique. With the aid of computer software called Microsoft Excel, data processing is carried out. The analysis's findings indicate that the agriculture sector is a developing one that has the potential to propel the downstream industry.